2021
DOI: 10.1016/j.cmi.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-day survival among older adults with severe infection with severe acute respiratory syndrome coronavirus 2 treated with corticosteroid: a cohort study

Abstract: on behalf of the COCO-OLD Study group. Writing committee, Methodology and statistics, Centres (alphabetically), 14-Day survival among older adults with severe SARS-Cov2 infection treated with corticosteroid: a cohort study, Clinical Microbiology and Infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 16 publications
0
15
0
4
Order By: Relevance
“… 18 The Abolghasemi et al 16 study reported the concomitant use of lopinavir/ritonavir, hydroxychloroquine, and an anti-inflammatory agent together with plasma therapy. Previous studies report some benefits from using these drugs in adult patients; 40 , 41 however, more studies are needed here to control this variable, although, in clinical practice, this is almost impossible when treating patients with severe disease. The only study that could control this variable was Libster et al 17 because it included patients only with early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 The Abolghasemi et al 16 study reported the concomitant use of lopinavir/ritonavir, hydroxychloroquine, and an anti-inflammatory agent together with plasma therapy. Previous studies report some benefits from using these drugs in adult patients; 40 , 41 however, more studies are needed here to control this variable, although, in clinical practice, this is almost impossible when treating patients with severe disease. The only study that could control this variable was Libster et al 17 because it included patients only with early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…18 The Abolghasemi et al 16 study reported the concomitant use of lopinavir/ritonavir, hydroxychloroquine, and an anti-inflammatory agent together with plasma therapy. Previous studies report some benefits from using these drugs in adult patients; 40,41 There is enough evidence proving that convalescent plasma administration does not have many severe adverse events in transfusion. [16][17][18][19]29,33 In contrast, more research is needed on the synergistic effect that plasma could have with other repositioning drugs, as has been demonstrated, for example, with the use of remdesivir, as has been published in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies were not specific for older populations and did not consider comorbidities and functional status of patients, which are powerful prognostic factors in geriatric patients. Two retrospective cohort studies including 143 ( 10 ) and 267 ( 11 ) patients (mean age 85 years) concluded an association of corticosteroids with reduced mortality (hazards ratio = 0.61 [95% CI 0.41–0.93] for in-hospital mortality and 0.67 [95% CI 0.46–0.99] for 14-day mortality, respectively ( 10 , 11 )). However, the size of the population was lower than in our study, and we performed a propensity-score analysis to balance baseline characteristics in the 2 groups before performing a logistic mixed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few data are available on the prognosis of older patients hospitalized for COVID-19 and receiving corticosteroids ( 9 ), and their results are heterogeneous. Two retrospective observational studies concluded a benefit of corticosteroids in COVID-19 for older patients ( 10 , 11 ), but subgroup analysis of RECOVERY trial data ( 7 ) did not find a significant difference in terms of mortality and ventilator-free days at 28 days between older adults patients (≥70 years old) who received corticosteroids and those who did not. Because of the high rate and severity of side effects of corticosteroids in the geriatric population ( 12 , 13 ), the risk/benefit balance could be even more questionable in the context of COVID-19 for this population.…”
mentioning
confidence: 99%
“…On the same hand, a secondary analysis of the COVIP study conducted on critically ill elderly patients with COVID-19 found an independent association of J o u r n a l P r e -p r o o f steroid use with increased mortality [50]. Conversely, corticosteroids were associated with a significant increase in the overall survival at day 14 in patients aged >80 years hospitalized for severe COVID-19 in a recent study conducted in 36 hospitals in France and Luxembourg [51].…”
Section: Efficacy Of Therapy Specifically Directed Against Sars Cov-2mentioning
confidence: 97%